Ansel's pharmaceutical dosage forms and drug delivery systems - Allen, Loyd V., Jr; McPherson, Timothy B. (Wolters Kluwer (India), 2005)
"The purpose of this text is to introduce pharmacy students to the principles, practices, and technologies applied in the preparation of pharmaceutical dosage forms and drug delivery systems. An integrated presentation is used in this textbook to demonstrate the interrelationships between pharmaceutical and biopharmaceutical principles, product design, formulation, manufacture, compounding, and the clinical application of the various dosage forms in patient care. Regulations and standards governing the manufacturing and compounding of pharmaceuticals are also presented"--